ANALISIS KEGAGALAN NOSE WHEEL STEERING SYSTEM PADA PESAWAT BOEING DENGAN MENGGUNAKAN METODE FAILURE MODE AND EFFECT ANALISYS - Anggawaty, Dwi; Mulyani, Sri; Rahmawati, Fajar Khanif (Vortex, 2022)
Aircfrat use nose wheel steering system when landing, take off and landing. In the research discuses the problem of nose wheel steering system B737 – 800 to minimize problems ini nose wheel steering system. The stage of this research are to study the work system of nose wheel steering. Then look for the cause of the problem using the FMEA analysis method. This research is based on data from AFML (aircraft Flight and Manual Log) of the B737 – 800 Aircraft from January 2020 to Junu 2021 at Lion Airline. The results showed that the problem of nose wheel steering system in the failure mode analysis process using FMEA method data in the highest RPN ( Risk priority Number) value is 175 with the case steering collar dan torQ link need lubrication and case Tire pressure that caused by the lack of lubrication on the component and different pressure in tire. Then it is necessary to do inspection before flight.